Pengaruh Locus Of Control Terhadap Kinerja Karyawan (Studi Pada Karyawan Di PT X) - Hermawan, Francisca; Kaban, Dicky Franciscus (Universitas Muhammadiyah Yogyakarta, 2014)
Research regarding employee performance has been made multiple times, however research regarding locus of control that affected employee performance has only been done a few times. The primary data for this research were acquired from the employee of PT X, located in Tomang, West Jakarta. Samples were collected and calculated using a simple random sampling, and the statistical method used to test each hypothesis is multilevel linear regression.The outcome of this research has shown that all tested hypothesis are acceptable. Internal locus of control have positive impact towards the employee performace, external locus of control alsohave positive impact towards the employee performace, and locus of control has simultaneously impacted the employee performance.